Real time simulation of tacking yachts: how best to counter the advantage of an upwind yacht - Spenkuch, T.; Turnock, S.; Scarponi, M.; Shenoi, A. (Procedia Engineering, 2010)
In this paper we introduce a new wake model (NWM) for sailing yachts capable of representing the complex wake flow. We implemented the NWM into the yacht fleet race simulator Robo-Race and examined the effect of significant improvements in capturing the wind environment of a covered yacht on its performance and tactics. Various position options were investigated for maximising or minimising damaging effect of the leading or following yacht and were presented two case studies comparing the individual yacht performances.